The effect of a prescription order requirement for pharmacist-administered vaccination on herpes zoster vaccination rates. Issue 4 (21st January 2019) - Tak, Casey R.; Gunning, Karen; Kim, Jaewhan; Sherwin, Catherine M.; Ruble, James H.; Nickman, Nancy A.; Biskupiak, Joseph E.
Abstract: Objective: To determine the effect of a prescription order requirement for pharmacist-administered zoster vaccination on zoster vaccination in adults aged 60+. Methods: A 50-state law review of statutes and regulations regarding pharmacists' ability to administer the zoster vaccine with/without a prescription order was performed. States were classified as prescription order required or not required as of January 1, 2014. Data on adults aged 60+ were obtained from the 2014 Behavioral Risk Factor Surveillance System (BRFSS). Chi-square tests and multilevel logistic regression models with and without propensity scores methods were used. Results: Of the 50 states, 39 and the District of Columbia did not require a prescription order. After propensity score matching, zoster vaccination rates for adults ages 60 and older were significantly higher in states that did not require a prescription order (23.0% vs 21.1%, p = 0.0022). The propensity score-matched multilevel logistic regression model for adults aged 60+ found modestly higher odds of HZ vaccination for states that removed the prescription order requirement (OR 1.17, 95% CI 1.01–1.35). Similar estimates were found across other methodologies employed and age strata, although statistical significance varied. Conclusions: Prescription order requirements are associated with HZ vaccination rates. By removing a prescription order requirement, states may be able to promote increases in HZ vaccination in adults aged 60+.